Rapid preparation device and method for gradient catalyst layer of membrane electrode of fuel cell
Through centrifugal sedimentation and hot pressing technology, the rapid preparation of the membrane electrode gradient catalytic layer is achieved, which solves the problem of difficult to achieve gradient catalytic layer in the prior art, improves the performance and stability of fuel cells, and reduces production costs. In mass production.
Patent Information
- Application Number
- CN202411074698.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-17
AI Technical Summary
The existing membrane electrode catalytic layer preparation method is difficult to achieve a gradient catalytic layer structure, resulting in the diffusion of reactants and the diffusion of products leaving the active catalytic point during the reaction process, which affects the performance and stability of fuel cells, and the spraying method is costly and production efficiency. Low, not suitable for mass production.
The membrane electrode gradient catalytic layer is prepared by centrifugal settlement. By controlling the vertical distribution of catalyst particles, the gradient distribution of catalyst and ionic polymer is achieved using centrifugal acceleration and time, and a gradient catalytic layer is formed in combination with hot pressing and drying technology.
The rapid batch preparation of the membrane electrode gradient catalytic layer is realized, the proton conduction performance and stability of the fuel cell is improved, the production cost is reduced, and it is suitable for large-scale production.
Smart Images

Figure CN119153710A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technology of preparing the structure of a fuel cell membrane electrode catalyst layer, and in particular relates to a device and method for quickly preparing a fuel cell membrane electrode gradient catalyst layer. Background Art
[0002] The preparation process of membrane electrode catalyst is crucial to the performance of fuel cells. At present, there are several common preparation methods, among which CCM (Catalyst Coated Membrane) is the most commonly used. This method directly coats the active components of the catalyst on both sides of the proton exchange membrane, effectively reducing the proton transfer resistance between the membrane and the catalyst layer. In addition, there are transfer printing, ion exchange reduction deposition, ultrasonic spraying and other technologies. However, these methods are all aimed at forming a structurally uniform catalytic layer on the proton membrane with the same slurry. However, the structurally uniform catalytic layer limits the diffusion of reactants to the catalytic layer and the diffusion of products away from the active catalytic point during the reaction, slowing down the catalytic reaction kinetics. In order to improve the performance of the membrane electrode, it is urgent to develop a three-dimensionally distributed catalytic layer to make full use of the catalyst performance per unit area and weight, so constructing a gradient catalytic layer is one of the ways to improve the catalytic performance. The gradient catalytic layer is a structure that can improve the performance and stability of fuel cells. Its gradually changing three-dimensional component structure regulates the distribution and activity of the catalyst.
[0003] There are many factors that affect the performance of proton exchange membrane electrode (MEA), but the main factors for materials are proton conductivity, catalyst layer structure, and drying process.
[0004] Proton conductivity plays a vital role in promoting proton transfer within the MEA, which in turn affects the overall performance of the fuel cell. In order to improve the proton conductivity of the membrane electrode, it is necessary to balance the content of the ionic polymer Nafion in the catalyst layer and design its distribution in a gradient. Because although the increase in the Nafion content can improve the proton conductivity, it will also reduce the porosity, which is not conducive to the transmission of gas and water. In addition, uniformly distributed catalyst particles are not an ideal structure for the electrode. If the Nafion content is increased on the side close to the proton membrane and the porosity is increased on the side close to the diffusion layer GDL cathode microporous layer, the performance of the membrane electrode can be effectively improved. The second is the catalyst layer (CL) structure, which is where the electrochemical reaction occurs and consists of platinum metal particles, ionic polymers and carbon carriers. The content and distribution of ionic polymers in the CL affect the performance of the MEA. The degradation of Pt particles, ionic polymers and carbon carriers will affect the power generation performance and durability of the MEA. Finally, the CL drying process in the membrane electrode manufacturing process refers to the process in which substances unrelated to the CL composition, such as alcohol dispersants, pore formers, water, etc., evaporate from the wet coating layer to form a solid dry coating layer after the slurry is coated on the substrate. After drying, the composition and distribution, porosity, hydrophilicity and hydrophobicity of the CL are basically determined. Therefore, the CL drying process is directly related to the performance, life and other indicators of MEA, and is very important for forming a three-dimensional porous structure of the electrode catalyst layer (CL) on the substrate based on the catalyst slurry.
[0005] According to existing public information, how to realize the gradient catalytic layer structure is a difficult problem that has been waiting to be solved in the industry. In order to realize the gradient catalytic layer, the existing technology is mostly spraying, that is, spraying catalyst slurries of different components onto the proton membrane in sequence to achieve the designed gradient distribution. The spraying equipment cooperates with one or more nozzles through the feeding system, and switches back and forth between them to realize the gradient catalytic layer. Although the spraying method is relatively simple, the cost of the spraying device is relatively high and is generally only suitable for laboratory research and development. In addition, because of its low production efficiency and serious waste of catalyst slurry, it is not suitable for mass production. There is no process design for gradient catalytic layer in the existing batch CCM production. Summary of the invention
[0006] In order to achieve rapid preparation of fuel cell membrane electrode gradient catalytic layer, the present invention provides a method for rapid preparation of fuel cell membrane electrode gradient catalytic layer. The second purpose of the present invention is to provide a method for rapid preparation of fuel cell membrane electrode gradient catalytic layer, and to achieve rapid preparation of fuel cell membrane electrode gradient catalytic layer by centrifugation.
[0007] Technical solution: A method for rapidly preparing a gradient catalyst layer of a fuel cell membrane electrode. In the method, during the preparation process of the fuel cell membrane electrode, the catalyst particles in the coated catalyst layer are allowed to settle by centrifugal sedimentation to form a gradient catalyst layer, and the solid catalyst particles and auxiliary material particles in the catalyst layer are vertically distributed in a gradient manner; the steps include:
[0008] S1. Catalytic layer slurry configuration, wherein the catalytic layer slurry comprises catalyst particles, an ionic polymer for reducing the viscosity of the catalytic layer slurry, and a solvent, wherein the solvent comprises a single or mixed solution of ethylene glycol, water, n-propanol, and isopropanol;
[0009] S2, spraying the catalyst layer slurry on the transfer membrane, and then fixing it to the drum in the horizontal centrifuge through a transfer fixture for centrifugal operation, controlling the centrifugal acceleration and the centrifugal time to determine the sedimentation rate of the catalyst particles in the catalyst layer, thereby achieving gradient control of the catalyst / ion polymer, and after obtaining a catalyst layer with a gradient distribution of the catalyst and ion polymer that meets the preparation requirements, heating, drying and curing the catalyst layer;
[0010] S3, stacking the transfer membrane containing the catalyst and the proton exchange membrane together, heating and pressing them in a hot press, and then transferring the catalyst from the transfer membrane to the target substrate, thereby obtaining a CCM with a gradient distribution of the catalyst layer;
[0011] The gradient of the catalyst and ionomer in the catalytic layer is determined by the centrifugal acceleration, centrifugal time, solid content and viscosity of the catalyst slurry.
[0012] The catalyst layer prepared by the method has a solid content of 3-20% in the catalyst layer slurry, and the viscosity of the slurry after adding the ion polymer is 50-300 Pa·s in a static state;
[0013] Centrifugal treatment, select the shortest time when the catalyst particle gradient tends to be stable as the centrifugal time, the centrifugal time is between 5 seconds and 5 minutes. The centrifugal acceleration is controlled at 10-1000m / s 2 . At the same time, the mass ratio of the ionomer to the carbon in the catalyst is controlled to be between 0.6 and 1.2 to complete the preparation of the catalyst layer;
[0014] The anode platinum loading in the catalyst layer prepared by the method is controlled to be 0.03-0.15 mg / cm 2 , cathode loading is controlled at 0.2-0.5mg / cm 2 .
[0015] Furthermore, after centrifugal acceleration, the relative distribution ratio of the catalyst particles in the upper, middle and lower layers along the direction of gravity acceleration is set to 0.25:0.5:0.75.
[0016] Furthermore, the method includes calculating the control parameters for the centrifugal operation:
[0017] The following calculation is used to control the centrifugal acceleration:
[0018] g=r*(2πn / 60)2
[0019] Where g is the centrifugal acceleration, r is the radius of the drum, and n is the rotation speed;
[0020] The centrifugal time is estimated by the wet thickness of the catalyst layer and the sedimentation rate of the catalyst particles in the liquid composed of the solvent and the ionic polymer, combined with the Stokes formula or its modified formula. Assuming that the slow sedimentation process is laminar flow, that is, the Reynolds parameter is less than 1, the friction force is calculated as F D =6πμRv, where μ is the viscosity of the liquid, R is the average radius of the catalyst particles, and v is the sinking velocity of the catalyst; when the sinking velocity of the catalyst particles approaches zero, the downward centrifugal force, upward buoyancy and friction acting on the catalyst particles reach a balance, and mg=F B +F D , where m is the mass of the particle, g is the centrifugal acceleration, and F D is the friction force, F B is buoyancy; because F B =ρ Liq Vg, where ρ Liq is the density of the liquid, the volume of the catalyst particles And m=ρ Sp V, where ρ Sp is the density of the catalyst particles, we can get ρ Sp Vg=ρ Liq Vg+6πμRυ; after sorting, we get:
[0021]
[0022] The time it takes for catalyst particles to reach the bottom layer from the surface layer in the wet coating layer Where ε is the average thickness of the wet layer;
[0023] The time required for centrifugal sedimentation is related to the difference between solid and liquid densities, the viscosity of the slurry, the particle size and the thickness of the wet coating layer. In actual operation, because the size of the catalyst particles is normally distributed, if the centrifugation time is estimated according to the average particle size, the content of large particles in the generated catalytic layer near the transfer membrane is higher than that of small particles. Therefore, based on the preparation operation control parameters obtained by the above calculation, in the resulting gradient catalytic layer structure, the catalyst activity also presents a gradient, which is beneficial to the life of the membrane electrode.
[0024] Furthermore, the heating and curing of the catalyst layer includes hot air drying or infrared drying, and the drying and curing is performed in a vacuum environment. The drying and curing includes the following two stages:
[0025] Thickening process: As the solvent evaporates, the slurry volume decreases and becomes viscous; when the slurry volume is reduced to about 30% of the wet state, the microporous forming process begins;
[0026] Micropore forming process: solid structure and micropores are formed between catalyst particles, and the movement of particles along the direction of gravitational acceleration is zero.
[0027] The present invention provides a device for rapidly preparing a fuel cell membrane electrode gradient catalyst layer, which is used to implement the above-mentioned method for rapidly preparing a fuel cell membrane electrode gradient catalyst layer, comprising:
[0028] A vacuum container, used to operate the catalyst layer in a vacuum environment;
[0029] The vacuum container is provided with a rotary drum and a horizontal centrifuge, and the rotary drum is used for centrifugal treatment of the catalyst layer slurry;
[0030] The vacuum container is also provided with a drying device, including an infrared dryer or a hot air dryer; the infrared drying heating tube is located at the center of the drum and is used to uniformly heat one or more transfer jigs;
[0031] The hot air inlet of the hot air drying equipment is a porous air duct located in the center of the drum, and there are multiple air outlets located on the drum wall, so as to facilitate the timely and uniform removal of the volatile solvent;
[0032] The drying device also includes an electric heater embedded in the transfer jig; heat is transferred to the bottom of the transfer film through the transfer jig, so that the solvent can evaporate stably and evenly;
[0033] The device also includes a control module for realizing acceleration control of the horizontal centrifuge and working time control of the drying equipment.
[0034] Furthermore, the vacuum container is made of a transparent material or is provided with a transparent observation window, so that the catalyst layer slurry and the morphology during centrifugation and curing or the color change of the solvent diffusion edge can be observed.
[0035] Furthermore, the device is also provided with a transfer jig, which is used to fix the transfer film on the drum in the horizontal centrifuge; the material of the transfer film includes a PET film configured as polytetrafluoroethylene or a PET film coated with tetrafluoroethylene.
[0036] Beneficial effects: The present invention realizes batch preparation of gradient catalytic layers by adding a centrifugal sedimentation process on the basis of a batch transfer production process, and can realize rapid preparation of catalytic layers. At the same time, the present invention combines theoretical and practical tests to optimize centrifugal acceleration and time, comprehensively considers the relationship between gradient and catalytic layer thickness, and comprehensively considers specific applications. Compared with the prior art, rapid preparation of catalytic layer gradient is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a process flow chart of the method of the present invention;
[0038] Figure 2 It is a structural schematic diagram of the device of the present invention. DETAILED DESCRIPTION
[0039] In order to explain the technical solution disclosed by the present invention in detail, a further introduction is given below in conjunction with the accompanying drawings and specific embodiments of the specification.
[0040] The present invention is aimed at the preparation problem of the catalyst layer on the membrane electrode of the fuel cell. By adding a centrifugal sedimentation process on the basis of the batch transfer production process, the batch preparation of the gradient catalyst layer is realized. After the catalyst is coated on the transfer membrane, a rotating centrifugal method is used to generate a supergravity environment while drying to increase the rapid sedimentation process, so that the catalyst particles in the catalyst layer after coating are settled to form a gradient catalyst layer. The drying method can be hot air drying, infrared drying, vacuum drying, etc., or a combination of the above methods. By characterizing the electrical properties of the final gradient catalyst layer and the profile of the catalyst layer, it is determined to optimize the centrifugal drying parameters such as centrifugal acceleration, centrifugal time, drying temperature, drying time, vacuum degree and other process parameters.
[0041] Specifically, combined Figure 1 and Figure 2 As shown, in order to realize the rapid preparation of the gradient catalyst layer of the fuel cell membrane electrode, the present invention adopts a centrifugal method to realize the gradient distribution of solid particles such as catalysts and auxiliary materials in the catalyst layer in the vertical direction. Figure 1 , which can be divided into three parts: conventional slurry preparation and coating process, centrifugation-drying process, and packaging process after transfer.
[0042] (1) First, the cathode and anode slurries are prepared. The slurries include catalyst particles, ionic polymers and solvents. The solvents include single or mixed solutions such as ethylene glycol, water, n-propanol, isopropanol, etc. The addition of ionic polymers reduces the viscosity of the slurry due to increased steric hindrance and electrostatic repulsion, and the slurry is thinned and converted into a Newtonian fluid through shear mixing. The final slurry is then controlled to have a solid content of 3-20% and a slurry viscosity of 50-300 Pa·s. Preferably, the solid content is between 8-15% and the slurry viscosity is between 100-200 cps. The slurry is then coated on a transfer membrane to form a catalytic layer. The transfer membrane is made of polytetrafluoroethylene or a PET film coated with tetrafluoroethylene on the surface. The anode loading of the catalytic layer finally formed is controlled to be 0.03-0.15 mg / cm 2 The cathode loading is controlled between 0.2-0.5 mg / cm 2 between;
[0043] (2) The transfer membrane coated with the catalytic layer is then fixed to the drum in the horizontal centrifuge by a transfer jig for centrifugal operation (such as Figure 2 ), and its centrifugal time and speed can be controlled by PLC. Due to the supergravity generated by centrifugation, the catalyst particles with higher density in the catalyst layer settle to the bottom and form a gradually increasing gradient, while the ionic polymers with relatively smaller density are displaced and form a trend of floating to the top and gradually increasing; in this way, a catalyst layer with a gradient distribution of catalyst and ionic polymer is obtained, with the bottom of the transfer membrane being mostly catalyst and having a high porosity, while the top of the catalyst layer is mostly ionic polymer. When the centrifugation reaches a certain time, the PLC is used to turn on the heating to cure and shape the catalyst layer. The heating method can be hot air drying, infrared drying, or applying a vacuum to speed up the curing process. It is easier to implement the hot air drying solution with more mature technology.
[0044] According to the Stokes formula, the particle descent speed is related to the particle radius r, the slurry viscosity η, the density difference between the catalyst and the solvent (ρ-ρ0), and the acceleration g. If you need to increase the descent speed, you can adjust the solution viscosity, the density of the solvent and the acceleration. However, the adjustment of the solution viscosity and the solvent density often means a change in the slurry formula, resulting in poor electrical properties and a small increase in the sedimentation speed. The particle sedimentation speed can be significantly accelerated by changing the acceleration.
[0045] The centrifugal acceleration and running time have a great influence on the catalyst gradient distribution. The centrifugal acceleration is calculated as g = r*(2πn / 60)2. Where g is the centrifugal acceleration (m / s 2)r is the radius of the drum (m), and n is the rotation speed (rpm, 1 / min); the radius is a device characteristic, and the centrifugal acceleration increases exponentially with the square of the rotation speed, so the centrifugal speed is the main control parameter of this patent; generally, the speed range of medium and low speed centrifugal equipment is 1,000-20,000rpm, preferably 5,000-10,000rpm.
[0046] The centrifugation time is estimated by the wet thickness of the catalyst layer and the sedimentation velocity of the catalyst particles in the liquid composed of solvent and ionomer, combined with Stokes formula (1) or its modified formula (3), assuming that the slow sedimentation process is laminar flow, that is, the Reynolds parameter is less than 1:
[0047] Friction force: FD = 6πμRυ (1)
[0048] Where μ is the viscosity of the liquid, R is the average radius of the catalyst particles, and υ is the sinking velocity of the catalyst. When the sinking velocity of the catalyst particles approaches zero, the downward centrifugal force (gravity), upward buoyancy, and friction acting on the catalyst particles reach a balance:
[0049] mg=FB+FD (2)
[0050] Where m is the mass of the particle, g is the centrifugal acceleration, FD is the friction force, and FB is the buoyancy force.
[0051] Because FB = ρLiqVg, where ρLiq is the density of the liquid and the volume of the particle
[0052] And m = ρSpV, where ρSp is the density of the catalyst particles and V is the volume of the particles; Substituting the above into formula (2) yields:
[0053] ρSpVg=ρLiqVg+6πμRυ;
[0054] After sorting, formula (3) is as follows:
[0055]
[0056] The time it takes for catalyst particles to reach the bottom layer from the surface layer in the wet coating layer:
[0057]
[0058] Where ε is the average thickness of the wet layer. It can be seen from equations (3) and (4) that the time required for centrifugal sedimentation is related to the difference between the solid and liquid densities, the viscosity of the slurry, the particle size and the thickness of the coated wet layer. In actual operation, the size of the catalyst particles is normally distributed. If the centrifugation time is estimated according to the average particle size, the content of large particles near the transfer membrane in the generated catalyst layer is higher than that of small particles. Therefore, in the gradient catalyst layer structure prepared by the present invention, the catalyst activity also presents a gradient, which is beneficial to the life of the membrane electrode.
[0059] The centrifugal acceleration is set during the implementation process by controlling the centrifugal speed. The catalyst particle settling velocity and the catalyst / ion polymer gradient in the catalyst layer can be determined by controlling the centrifugal acceleration and the centrifugal time. The centrifugal time can be estimated by the wet thickness of the catalyst layer and the particle settling velocity; the centrifugal acceleration is controlled at 10-1000m / s 2 The centrifugal time is controlled between 5s and 300s. Preferably, the centrifugal acceleration is controlled between 50 and 500m 2 / s, and the centrifugal time is controlled between 10s-100s.
[0060] Drying time and degree of drying. Proper drying ensures uniform CL formation and prevents structural defects, while avoiding changes in the catalytic layer gradient caused by the transfer process. However, challenges exist in the process: too fast drying speed will cause boiling and peeling of the catalytic layer surface, while slow drying may lead to low efficiency. The drying method of the present invention is a continuous steady-state drying process, which is to place the coated transfer film on a centrifugal drum fixture, and use infrared or convection heating while centrifuging to generate a catalytic layer gradient.
[0061] Preferably, drying will use convection heating under vacuum. The drying time is about 10s to 10min, and the hot air drying temperature is about 50℃-100℃; the drying wind speed and air volume will be adjusted according to the equipment capacity.
[0062] Drying and fixing includes the following two stages:
[0063] Thickening process: As the liquid solvent gradually evaporates, the slurry volume decreases and the slurry becomes viscous; when the slurry volume is reduced to about 30% of the wet state, the microporous forming process begins;
[0064] Micropore forming process: solid structure and micropores are formed between catalyst particles, and the movement of particles in the direction of gravity acceleration is zero;
[0065] It is further pointed out that the drying conditions should be selected with the goal of uniform volatilization of the solvent and uniform distribution of particles on the surface of the catalyst layer. Experimental observations have shown that the drying time is first related to the drying temperature, vacuum degree, and humidity in the centrifugal chamber. In general, the drying temperature is selected to be lower than the boiling point of the solvent to avoid explosion caused by local boiling on the surface of the catalyst layer; secondly, the vacuum degree is set at 102-10 -1 Pa, this is to shorten the drying time while avoiding boiling of the solvent; the humidity in the centrifugal chamber or the partial pressure of the solvent affects the volatilization of the solvent, because the volatilization of the solvent from the liquid phase to the gas phase is affected by the humidity or the partial pressure of the solvent. The method of controlling the humidity can be to introduce a dry gas, such as nitrogen, into the centrifugal chamber to control it.
[0066] Secondly, the drying time is related to the weight ratio of ionomer: carbon in the catalyst (IC ratio). Generally speaking, the larger the IC ratio, the larger the ionomer weight ratio, and the longer the drying time. However, a too small IC ratio will negatively affect the dispersion of the catalyst in the slurry and the performance of the membrane electrode. Therefore, considering various factors, the IC ratio of the slurry is selected to be between 0.5 and 1.5, and the preferred IC ratio is between 0.6 and 1.2.
[0067] Finally, the drying time needs to be determined experimentally. The experimental method is to first transfer 1 mL of slurry to the transfer membrane with a pipette, place the formed slurry circular spot in a bell jar under a predetermined temperature, vacuum and humidity, and use an optical microscope to observe and record the slurry thickening process and micropore forming process. The drying time of slurries with different IC ratios is different. Generally, the thickening process takes 60 to 90% of the time, and the micropore forming process takes 10 to 40% of the time. The principle of selecting the drying time is that the edge of the slurry circular spot is smooth after drying, and the thickness of the circular spot in the diameter direction varies within 10%. The drying time determined by the experiment will be used as the initial setting of the centrifugal equipment, but the formal production process will be finally confirmed based on the performance of the packaged membrane electrode.
[0068] (3) Finally, the cathode and anode catalyst layers are transferred to the proton exchange membrane by hot pressing, that is, the transfer membrane containing the catalyst is superimposed on the proton exchange membrane and heated and pressed in a hot press. In this process, the catalyst is transferred from the transfer membrane to the target substrate. In this way, a CCM with a gradient distribution of the catalyst layer is obtained.
[0069] The prepared CCM is frame-encapsulated and GDL-encapsulated to obtain a membrane electrode containing a gradient catalytic layer. The optimized centrifugal and drying parameters can be selected by testing the performance of the membrane electrode at different centrifugal accelerations and centrifugal times.
[0070] Example 1 (high centrifugal acceleration, short centrifugal time, low temperature hot air heating)
[0071] The anode is prepared with slurry according to a solid content of 10%, a Pt / C catalyst with a Pt content of 20%, a ratio of ion polymer to carbon of 1:1, and a ratio of solvent alcohol to water of 1:1; the cathode is prepared with slurry according to a solid content of 15%, a Pt / C catalyst with a Pt content of 50%, a ratio of ion polymer to carbon of 1:1, and a ratio of solvent alcohol to water of 1:1;
[0072] The cathode and anode slurries were coated on the PTFE membrane respectively, and the anode Pt loading was controlled to 0.15 mg / cm 2 , cathode Pt loading 0.45mg / cm 2 ;
[0073] The membrane coated with the catalyst slurry was transferred to a centrifugal dryer, and the centrifugal speed was set to 10000rpm and the centrifugal time was set to 10s; then hot air drying was adopted, and the drying temperature was 60℃ and the time was 3min; the centrifugal parameters of the anode and cathode drying were the same;
[0074] The PTFE membrane containing the cathode and anode catalyst layers and the proton membrane are clamped together and placed in a hot press for hot pressing transfer at a temperature of 120°C for 30 seconds to obtain a gradient CCM. The CCM is encapsulated to obtain a membrane electrode containing a gradient catalyst layer.
[0075] Example 2 (Low centrifugal acceleration, long centrifugal time, high temperature hot air heating)
[0076] The anode is prepared with slurry according to a solid content of 10%, a Pt / C catalyst with a Pt content of 20%, a ratio of ion polymer to carbon of 1:1, and a ratio of solvent alcohol to water of 1:1; the cathode is prepared with slurry according to a solid content of 15%, a Pt / C catalyst with a Pt content of 50%, a ratio of ion polymer to carbon of 1:1, and a ratio of solvent alcohol to water of 1:1;
[0077] The cathode and anode slurries were coated on the PTFE membrane respectively, and the anode Pt loading was controlled to 0.15 mg / cm 2 , cathode Pt loading 0.45mg / cm 2 ;
[0078] The membrane coated with the catalyst slurry was transferred to a centrifugal dryer, and the centrifugal speed was set to 5000 rpm and the centrifugal time was set to 5 min. Then, hot air drying was performed at a drying temperature of 90°C and a time of 1 min. The centrifugal parameters for the anode and cathode drying were the same.
[0079] The PTFE membrane containing the cathode and anode catalyst layers and the proton membrane are clamped together and placed in a hot press for hot pressing transfer. The hot pressing temperature is 120°C and the time is 30s to obtain a gradient CCM. The CCM is encapsulated to obtain a membrane electrode containing a gradient catalyst layer.
[0080] Example 3 (high centrifugal acceleration, long time centrifugation, infrared drying and heating)
[0081] The anode is prepared with slurry according to a solid content of 10%, a Pt / C catalyst with a Pt content of 20%, a ratio of ion polymer to carbon of 1:1, and a ratio of solvent alcohol to water of 1:1; the cathode is prepared with slurry according to a solid content of 15%, a Pt / C catalyst with a Pt content of 50%, a ratio of ion polymer to carbon of 1:1, and a ratio of solvent alcohol to water of 1:1;
[0082] The cathode and anode slurries were coated on the PTFE membrane respectively, and the anode Pt loading was controlled to 0.15 mg / cm 2 , cathode Pt loading 0.45mg / cm 2 ;
[0083] The membrane coated with the catalyst slurry was transferred to a centrifugal dryer, and the centrifugal speed was set to 5000 rpm and the centrifugal time was 5 min. Then infrared drying was adopted, with a drying power of 300 W, a light source distance of 20 cm, and a time of 1 min. The centrifugal parameters for the cathode and anode drying were the same.
[0084] The PTFE membrane containing the cathode and anode catalyst layers and the proton membrane are clamped together and placed in a hot press for hot pressing transfer at a temperature of 120°C for 30 seconds to obtain a gradient CCM. The CCM is encapsulated to obtain a membrane electrode containing a gradient catalyst layer.
Claims
1. A method for rapidly preparing a gradient catalyst layer of a fuel cell membrane electrode, characterized in that: In the preparation process of the fuel cell membrane electrode, the method uses centrifugal sedimentation to make the catalyst particles in the coated catalyst layer settle to form a gradient catalyst layer, and realizes that the solid catalyst particles and auxiliary material particles in the catalyst layer are distributed in a gradient in the vertical direction; The implementation steps of the method include: S1. Catalytic layer slurry configuration, wherein the catalytic layer slurry comprises catalyst particles, an ionic polymer for adjusting the viscosity of the catalytic layer slurry, and a solvent, wherein the solvent comprises a single or mixed solution of ethylene glycol, water, n-propanol, and isopropanol; S2, coating the catalyst layer slurry on the transfer membrane, and then fixing it to the drum in the centrifuge through a transfer fixture for centrifugal operation, controlling the centrifugal acceleration and the centrifugal time to determine the sedimentation rate of the catalyst particles in the catalyst layer, thereby achieving gradient control of the catalyst / ion polymer, and after obtaining a catalyst layer with a gradient distribution of the catalyst and ion polymer that meets the preparation requirements, heating, drying and curing the catalyst layer; S3, stacking the transfer membrane containing the catalyst and the proton exchange membrane together, heating and pressing them in a hot press, and then transferring the catalyst from the transfer membrane to the target substrate, thereby obtaining a CCM with a gradient distribution of the catalyst layer; The gradient of the catalyst and ionomer in the catalytic layer is determined by the centrifugal acceleration, centrifugal time, solid content and viscosity of the catalyst slurry.
2. The method for rapidly preparing a fuel cell membrane electrode gradient catalytic layer according to claim 1, characterized in that: The solid content of the catalyst layer slurry is between 3-20%, and the viscosity of the slurry after adding the ion polymer is 50-300 Pa·s at rest; Centrifugal treatment, selecting the shortest time for the catalyst particle gradient to be stable as the centrifugal time, and controlling the mass ratio of the ion polymer to the carbon in the catalyst to be between 0.6 and 1.2 to complete the preparation of the catalyst layer; The anode platinum loading in the catalyst layer prepared by the method is controlled to be 0.03-0.15 mg / cm 2 , cathode loading is controlled at 0.2-0.5mg / cm 2 .
3. The method for rapidly preparing a fuel cell membrane electrode gradient catalytic layer according to claim 1 or 2, characterized in that: After centrifugal acceleration, the relative distribution ratio of the catalyst particles in the upper, middle and lower layers along the gravity acceleration direction is set to 0.25:0.5:0.75, at which time the centrifugal force is balanced with the buoyancy of the particles in the slurry and the friction with the slurry.
4. The method for rapidly preparing a fuel cell membrane electrode gradient catalytic layer according to claim 1 or 2, characterized in that: The centrifugal acceleration is 10-1000m / s 2 .
5. The method for rapidly preparing a fuel cell membrane electrode gradient catalytic layer according to claim 1 or 2, characterized in that: The centrifugation time was controlled between 5 seconds and 5 minutes.
6. The method for rapidly preparing a fuel cell membrane electrode gradient catalytic layer according to claim 1, characterized in that: The control parameter calculation of the centrifugal operation in this method includes: The following calculation is used to control the centrifugal acceleration: g=r*(2πn / 60)2 Where g is the centrifugal acceleration, r is the radius of the drum, and n is the rotation speed; The centrifugal time is estimated by the wet thickness of the catalyst layer and the sedimentation rate of the catalyst particles in the liquid composed of the solvent and the ionic polymer, combined with the Stokes formula or its modified formula. Assuming that the slow sedimentation process is laminar flow, the corresponding Reynolds parameter is less than 1. At this time, the friction force is calculated as F D =6πμRv, where μ is the viscosity of the liquid, R is the average radius of the catalyst particles, and v is the sinking velocity of the catalyst; when the sinking velocity of the catalyst particles approaches zero, the downward centrifugal force, upward buoyancy and friction acting on the catalyst particles reach a balance, and mg=F B +F D , where m is the mass of the particle, g is the centrifugal acceleration, and F D is the friction force, F B is buoyancy; because F B =ρ Liq Vg, where ρ Liq is the density of the liquid, the volume of the catalyst particles And m=ρ Sp V, where ρ Sp is the density of the catalyst particles, we can get ρ Sp Vg=ρ Liq Vg+6πμRυ; after sorting, we get: The time it takes for catalyst particles to reach the bottom layer from the surface layer in the wet coating layer ε is the average thickness of the wet layer; The time required for centrifugal sedimentation is related to the difference between solid and liquid densities, the viscosity of the slurry, the particle size and the thickness of the wet coating layer. In actual operation, because the size of the catalyst particles is normally distributed, if the centrifugation time is estimated according to the average particle size, the content of large particles in the generated catalytic layer near the transfer membrane is higher than that of small particles. Therefore, based on the preparation operation control parameters obtained by the above calculation, in the resulting gradient catalytic layer structure, the catalyst activity also presents a gradient, which is beneficial to the life of the membrane electrode.
7. The method for rapidly preparing a fuel cell membrane electrode gradient catalytic layer according to claim 1, characterized in that: The heating curing of the catalyst layer includes hot air drying or infrared drying, and the drying and curing is carried out in a vacuum environment. The drying and curing includes the following two stages: Thickening process: As the solvent evaporates, the slurry volume decreases and becomes viscous; when the slurry volume is reduced to about 30% of the wet state, the microporous forming process begins; Micropore forming process: solid structure and micropores are formed between catalyst particles, and the movement of particles along the direction of gravitational acceleration is zero.
8. A rapid preparation device for a fuel cell membrane electrode gradient catalyst layer, characterized in that: The method for rapidly preparing a fuel cell membrane electrode gradient catalyst layer according to any one of claims 1 to 7 comprises: A vacuum container, used to operate the catalyst layer in a vacuum environment; The vacuum container is provided with a rotary drum and a horizontal centrifuge, and the rotary drum is used for centrifugal treatment of the catalyst layer slurry; The vacuum container is also provided with a drying device, including an infrared dryer or a hot air dryer; the infrared drying heating tube is located at the center of the drum and is used to uniformly heat one or more transfer jigs; The hot air inlet of the hot air drying equipment is a porous air duct located in the center of the drum, and there are multiple air outlets located on the drum wall, so as to facilitate the timely and uniform removal of the volatile solvent; The drying device also includes an electric heater embedded in the transfer jig; heat is transferred to the bottom of the transfer film through the transfer jig, so that the solvent can evaporate stably and evenly; The device also includes a control module for realizing acceleration control of the horizontal centrifuge and working time control of the drying equipment.
9. The rapid preparation device for a fuel cell membrane electrode gradient catalyst layer according to claim 8, characterized in that: The vacuum container is made of a transparent material or is provided with a transparent observation window, so that the catalyst layer slurry and the shape during centrifugation and curing or the color change of the solvent diffusion edge can be observed.
10. The fuel cell membrane electrode gradient catalyst layer rapid preparation device according to claim 8, characterized in that: The device is also provided with a transfer jig, which is used to fix the transfer film on the drum in the horizontal centrifuge; the material of the transfer film includes a PET film made of polytetrafluoroethylene or coated with polytetrafluoroethylene.
Citation Information
Cited By
Regulation and control method and system for dynamic dispersion of catalyst slurry ionomer of hydrogen fuel cell
CN120072961A
